2004
DOI: 10.1023/b:biry.0000026201.71587.a2
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase Iota-Like Activity in Crude Cell Extracts of Different Mouse Organs

Abstract: The recently discovered DNA polymerase iota differs greatly from the numerous eukaryotic and prokaryotic DNA polymerases known previously in its ability to catalyze error-prone DNA synthesis. Using homogeneous preparations of the enzyme, it was shown previously that DNA polymerase iota incorporated preferentially dGMP opposite the thymidine of the template in the growing DNA chain. To elucidate the role of this enzyme in the mammals, its activity was assayed in crude cell extracts of different mouse organs. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Our results showed that the activity of this enzyme in mouse brain cells is significantly greater than in the majority of other organs [5]. This finding suggests that the high activity of Pol ι in mouse brain cells should play a functional role.…”
Section: Discussionsupporting
confidence: 45%
See 4 more Smart Citations
“…Our results showed that the activity of this enzyme in mouse brain cells is significantly greater than in the majority of other organs [5]. This finding suggests that the high activity of Pol ι in mouse brain cells should play a functional role.…”
Section: Discussionsupporting
confidence: 45%
“…The analysis of cell extracts of mouse liver, heart, lungs, spleen, and pancreas, performed under the same conditions as the analysis of brain cell extracts, did not reveal Pol ι activity [5], although other DNA polymeras es were detected well under these conditions.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations